Karakteristik Kimia Nori Analog Berbasis Genjer (Limnocharis flava) dan Albedo Semangka (Citrullus lanatus) - Lestari, Tiara Amanda; Iznilillah, Wilna; Khadijah, Neng Siti; Nurlaela, Raden Siti; Puspasari, Erna (Universitas Djuanda, 2024)
Commercial nori is made from the main ingredient of Porphyra seaweed which is not found in Indonesia, so most nori is an imported product. Nori analogues were created as an alternative to commercial nori. This research aims to make nori analogues made from watermelon genjer and albedo that have chemical properties close to commercial nori. This study used a One-Factor Complete Randomized Design, namely the nori formulation with 7 levels of treatment and two repeats. The nori formulation was obtained using the Expert Design 13 Mixture D-Optimal method with minimum and maximum limit factors given at watermelon albedo concentrations (50%-80%) and genjer (20%-50%). The resulting analog nori was tasted of chemistry characteristic. Data analysis in this study used the Expert 13 Design program and the SPSS program with statistical tests, namely the fingerprint test (ANOVA) and Duncan's follow-up test at a 95% confidence interval. The selected analogue nori formulation in the Expert 13 Design program based on chemical test results is nori made from 70% watermelon albedo: 30% genjer: 0.9% carrageenan: 1.5% flavoring: 0.2% citric acid. This analogue nori contains 5.2% moisture content, 5.6% ash content, and 22.9% crude fiber content.